Fast preparation of photopolymerized monolithic columns for capillary electrochromatography - Gong, Wen-jun; Xu, Guang-ri; Zhang, Yi-jun; Zhang, Yu-ping; Choi, Seong-ho; Lee, Kwang-pill (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2008)
Photopolymerized sol-gel(PSG) columns were prepared using methacryloxypropyltrimethoxysilane as the monomer, toluene as the porogen and hydrochloric acid as the catalyst. Four different photoinitiators such as benzoin methyl ether, Irgacure 819, Irgacure 1700 and Irgacure 1800 were comparatively used in the reaction solution in the presence and absence of sodium dodecyl sulfate. The above eight solutions were respectively irradiated at 365 nm for 5–10 min in each capillary (75 μm inside diameter) to prepare the porous monolithic sol-gel column by a one-step, in situ, process. The chromatographic behavior of the eight PSG columns were comparatively studied, all of which exhibit reversed-phase character. Using these columns, several neutral compounds, namely thiourea, benzene, toluene, ethyl benzene, biphenyl and naphthalene can be separated from mixtures with a largest column efficiency of 74 470 plate/column for thiourea. Addition of sodium dodecyl sulfate in the polymerization process has a significant influence on the morphology and migration time.